Foreword - Andaleeb, Syed Saad (IGI Global, 2018)
This editorial was presented in the Human Development and Interaction in the book Age of Ubiquitous Technology; 27 June 2016, Page xiii[© 2016 IGI Global] The editorial's definite version is available at: http://dx.doi.org/10.4018/978-1-5225-0556-3 The book's definite version is available at: https://www.igi-global.com/gateway/book/147105